Ceiling on landholdings - George P. T. (Hyderabad, 1981)
This book is related to utilization of surplus land. This book covers the following topics Socio-economic background of the sample groups; Allotted land and its utilisation; land development; cropping pattern and results of cultivation; Total Income and per capita income; cost of cultivation and returns from farm operations etc.
Keywords: Socio Economic